Analisis Hubungan Lama Pengunaan Gadget dengan Tingkat Stress Mahasiswa - Renaldy Angkasa; Palma Juanta; Gabriella Halim (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyze the relationship between the duration of use of gadgets and stress levels in Prima Indonesia University students. In the current digital era, the use of gadgets has become an inseparable part of the daily life of students, both for academic purposes, entertainment, and social communication. However, excessive use of gadgets can have a negative impact on mental health, especially in terms of increasing stress levels.It is feared that the use of gadgets among students can trigger various psychological problems, especially when students are faced with high academic pressure, college assignments, and the need to continue to be connected online. Therefore, it is important to understand the extent of the duration of the use of gadgets to contribute to the stress experienced. The research method used is a quantitative survey, with questionnaires distributed to 50 students from various majors, such as economics, information systems, informatics engineering, and medicine. The data collected was analyzed using the Pearson correlation test and regression analysis. The results showed a positive and significant relationship between the length of use of gadgets and stress levels. Students who use gadgets for a longer time tend to have a higher stress level. This finding is expected to be the basis for the development of intervention programs that aim to reduce student stress through wise and healthy management of gadgets.